Porous Ceramics Membrane Preparation from Ternary Mixtures of Ranong Kaolin, Calcium Carbonate and Silica - Darunee, B.; Nucharee, C.; Tripob, B. (Journal of Applied Membrane Science & Technology, 2017)
Porous ceramics membranes were prepared from ternary mixtures of Ranong kaolin, calcium carbonate and silica using slip casting technique. Totally 10 different composition mixtures were selected from the ternary diagram of CaCO3 : SiO2 : Clay with weight fraction of 0–0.19 : 0.28–0.47 : 0.52–0.71, respectively. The ceramic paste was first fired at 800°C and then sintered at temperatures of 1200, 1250 and 1300°C. The results show that firing temperature above 1200°C is probably too high to prepare the porous ceramics of the studied compositions. The porosity less than 26% is obtained from the samples sintered at 1250–1300°C. The highest porosities of more than 40% are observed from the samples sintered at 1200°C with the weight fraction of clay, calcium carbonate and silica between 0.524–0.562, 0.076–0.152, and 0.310–0.394, respectively. In this range of compositions, the linear shrinkage and water absorption is about 3% and 22%, respectively, while the bending strength is between 28–30 MPa. The pure water flux of samples prepared from mixture formula 9 sintered at 1200°C ranges between 52.4 and 368.8 L/m2.h at the operating pressures 30–120 kPa, indicating that the mixture compositions nearby the formula 9 are the best for porous ceramic production using Ranong kaolin.